PERBEDAAN BENTUK LUKISAN SIDIK JARI, RIDGE COUNT, PALMAR PATTERN DAN SUDUT A-T-D ANTARA ORANG TUA ANAK SUMBING DENGAN ORANG TUA ANAK NORMAL DI TIMOR TENGAH SELATAN, NUSA TENGGARA TIMUR - Iriane, Vincentia Maria; Sanjoto, Pudjo; Loekito, Retno M. (Jurnal Kedokteran Brawijaya, 2003)
ABSTRACT The skin and lip-palate are formed nearly at the same period. They might be influenced by the similar genetic factor and environment.The  objective  of  this  research  is  to  find  the  difference  of  dermatoglyphi  between  cleft-lip  children’s  parents  and  normal  childern’sparents.  The  research  is  an  analytical  observation.  It  takes  50  samples  of  cleft-lip  children’s  parents  and  50  samples  of  normalchildren’s  parents.  Each  sample  is  classified  into  two  groups,  that  is,  (25)  fathers  and  (25)  mothers.  Finger  pattern,  ridge  count,palmar  patern  and  a-t-d  angle  are  dermatoglyphi  variables  to  be  measured.  He  result  shows  that:  (1)  The  relationship  betweenfather’s dermatoglifi and cleft-lip children is stronger than that between mother’s dermatoglifi and cleft-lif childern. (2) The percentageof whorl (W) pattern is higher in cleft-lip children’s parents; ehile the percentage of ulnar loop (UL)pattern is higher in normal children’sparents.  (3)  The  ridge  count  of  cleft-lip  children’s  fathers  is  normally  higher  than  that  of  normal  children’s  fathers.  (4)  There  is  nodifference  found  in  palmar  pattern  between  cleft-lip  children’parents  and  normal  children’s  parents.  (5)  A-t-d  angle  of  the  cleft  lipschildren’s fathers is bigger than that of normal children’s fathers. (6) Cleft lips in South East Timor, East Nusa Tenggara is ancertrallyinherited. Key words: Dermatoglyphies, cleft lip patients parent